NahY, a Catabolic Plasmid-Encoded Receptor Required for Chemotaxis of Pseudomonas putida to the Aromatic Hydrocarbon Naphthalene - Grimm, Ann C. (American Society for Microbiology, 1999)
Pseudomonas putida G7 exhibits chemotaxis to naphthalene, but the molecular basis for this was not known. A new gene, nahY, was found to be cotranscribed with meta cleavage pathway genes on the NAH7 catabolic plasmid for naphthalene degradation. The nahY gene encodes a 538-amino-acid protein with a membrane topology and a C-terminal region that resemble those of chemotaxis transducer proteins. A P. putida G7 nahY mutant grew on naphthalene but was not chemotactic to this aromatic hydrocarbon. The protein NahY thus appears to function as a chemoreceptor for naphthalene or a related compound. The presence of nahY on a catabolic plasmid implies that chemotaxis may facilitate biodegradation.